FACTORS CAUSING FOREST AND PEATLAND FIRES IN KAYU AGUNG DISTRICT, OGAN KOMERING ILIR REGENCY, SOUTH SUMATRA PROVINCE - Yuli Rosianty; Sasua Hustati Syahroni, S.P, M.Si; Windy Meysari (Universitas Muhammadiyah Palembang, 2026)
Forest and land fires are events that can be triggered by human activities or factors that occur without intentional elements. Fires in forest and peatland areas have a significant impact on environmental quality, including causing degradation of peat ecosystems, reducing the land's ability to absorb carbon, and causing health problems for communities living around the affected areas. This study aims to identify and analyze the factors that influence the occurrence of forest and peatland fires in Kayu Agung District, Ogan Komering Ilir Regency, fire mitigation that has been implemented in the area. The study was conducted in Kedaton and Kutaraya Villages, Kayu Agung District, Ogan Komering Ilir Regency. The method used is qualitative research supported by a quantitative approach. Data collection was carried out through observation, interviews, documentation, and questionnaires, while data analysis was carried out using frequency tables combined with descriptive analysis. The results of the study indicate that the dominant factor causing forest and peatland fires is the practice of land clearing by burning, while the influence of natural factors on fire occurrences is relatively small. Fire control efforts that have been undertaken are still not optimal, as they have largely focused on building canal barriers and clearing fuel beneath forest stands and peatlands.